Chronic oxidative stress promotes GADD34-mediated phosphorylation of the TAR DNA-binding protein TDP-43, a modification linked to neurodegeneration - Goh, Catherine Wenhui (2018)
Oxidative and endoplasmic reticulum (ER) stresses are hallmarks of the pathophysiology of ALS and other neurodegenerative diseases. In these stresses, different kinases phosphorylate eukaryotic initiation factor eIF2α, enabling the translation of stress response genes; among these is GADD34, the protein product of which recruits the α-isoform of protein phosphatase 1 catalytic subunit (PP1α) and eIF2α to assemble a phosphatase complex catalyzing eIF2α dephosphorylation and resumption of protein synthesis. Aberrations in this pathway underlie the aforementioned disorders. Previous observations indicating that GADD34 is induced by arsenite, a thiol-directed oxidative stressor, in the absence of eIF2α phosphorylation suggest other roles for GADD34. Here, we report that arsenite-induced oxidative stress differs from thapsigargin- or tunicamycin-induced ER stress in promoting GADD34 transcription and the preferential translation of its mRNA in the absence of eIF2α phosphorylation. Arsenite also stabilized GADD34 protein, slowing its degradation. In response to oxidative stress, but not ER stress, GADD34 recruited TDP-43, and enhanced cytoplasmic distribution and cysteine modifications of TDP-43 promoted its binding to GADD34. Arsenite also recruited a TDP-43 kinase, casein kinase-1ϵ (CK1ϵ), to GADD34. Concomitant with TDP-43 aggregation and proteolysis after prolonged arsenite exposure, GADD34-bound CK1ϵ catalyzed TDP-43 phosphorylations at serines 409/410, which were diminished or absent in GADD34−/− cells. Our findings highlight that the phosphatase regulator, GADD34, also functions as a kinase scaffold in response to chronic oxidative stress and recruits CK1ϵ and oxidized TDP-43 to facilitate its phosphorylation, as seen in TDP-43 proteinopathies.